Pelatihan Leadership sebagai Strategi Pengembangan Soft Skills Siswa SMK Islam Raudlatul Husna Lombok Tengah - Ramdani, Rizal; Yuliana, Ika; Alpiansah, Restu; Assa'ady, M. Chothibul Umam; Pratama, Aryan Agus (Insan Kreasi Media, 2025)
This community service activity aimed to equip students of SMK Islam Raudlatul Husna in Central Lombok with essential skills in effective communication, self-confidence, teamwork, and motivation in preparing for life after graduation. The program was initiated in response to a common challenge faced by today’s youth: the declining strength of leadership character, which often results in low self-confidence, poor communication abilities, and limited career development opportunities. As a solution, the organizing team collaborated with the Teman Bumigora community to conduct a leadership training program tailored for the students. This training was designed as a foundational step in developing strong leadership character. The program was attended by 33 students from the 12th grade (final semester) of SMK Islam Raudlatul Husna. In addition to sessions delivered by expert speakers, participants were also guided by facilitators through interactive discussions covering key topics such as leadership concepts, styles, and value, as well as responsibility and integrity in leadership roles. Therefore, following the completion of this program, students exhibited significant improvement in self-management, increased optimism, and enhanced confidence and communication skill from the leadership foundation they had acquired.